To what extent does the European common agricultural policy affect key landscape determinants of biodiversity?. Issue 114 (December 2020) - Pardo, Adara; Rolo, Víctor; Concepción, Elena D.; Díaz, Mario; Kazakova, Yanka; Stefanova, Vyara; Marsden, Katrina; Brandt, Katharina; Jay, Marion; Piskol, Stephan; Oppermann, Rainer; Schraml, Antonia; et al.
Highlights: Green and Blue Infrastructure (GBI) occurrence and change over time is quantified. We cover different farming systems in Southwest, Central and Southeast Europe. CAP is not actively encouraging the establishment of new biodiversity-fostering GBI. GBI most valuable for biodiversity like grasslands have significantly decreased. Farmers' perception of GBI seems driven by production management decisions. Abstract: Agricultural intensification continues to threaten habitat and biological diversity in farmland. In Europe, the Common Agricultural Policy (CAP) has established several measures to support biodiversity-fostering elements such as landscape features, semi-natural habitats and extensive land uses, together referred to as Green and Blue Infrastructure (GBI). However, CAP measures' effectiveness to support GBI has not been accurately evaluated yet. We assess GBI occurrence across a variety of European agricultural systems covering a gradient of farming intensity and analyse to what extent the CAP is supporting their presence by enhancing farmer's awareness and the uptake of measures that foster GBI. We carried out habitat surveys in 115 Landscape Test Squares (LTS) of 500m × 500m in six case study areas, including arable land, pastures and mixed farming systems in Spain, Germany and Bulgaria. We mapped GBI including small landscape elements, in-field elements (both semi-natural and productive) and connectivity features. We used historical imagery to map changes on GBI occurrence in LTS from 2012 to 2018. We also used questionnaires with farmers and stakeholders on their GBI awareness and compared their answers to elements mapped. Results showed that landscape and in-field GBI occurrence was higher in extensive than in intensive farming systems regardless of the region, whereas the opposite was found for connectivity features (e.g. grassy strips). The analysis of habitat changes showed a small increase of certain biodiversity-fostering in-field GBI, but no substantial change in connectivity features or landscape elements. Moreover, a significant reduction of valuable GBI like grasslands was observed. There were several mismatches between the patterns of GBI identified by farmers and stakeholders and their mapped abundances. Our results indicate that the CAP has not substantially increased the availability of biodiversity-fostering GBI in these regions and that adopted features were mostly related to neutral or negative effects on biodiversity. Farmers' perception of GBI features seems driven by production management decisions rather than by biodiversity concerns.